Formation and Containment Control for High-order Linear Swarm Systems - Dong, Xiwang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book focuses on analysis and design problems for high-order linear time-invariant (LTI) swarm systems (multi-agent systems) to achieve consensus, formation, containment and formation-containment. As a first step, the concepts of practical consensus and formation-containment are introduced. Unlike previous research, the formation in this book can be time-varying. A general framework for consensus, consensus tracking, formation, containment and state formation-containment is presented for the first time. Sufficient/necessary and sufficient conditions, and approaches to designing the protocols for swarm systems to achieve these control objectives, are respectively proposed. Autonomous time-varying formation experiments using five quadrotor unmanned aerial vehicles (UAVs) are conducted in an outdoor setting to demonstrate the theoretical results.
Introduction -- Preliminaries -- Consensus control of swarm systems -- Formation control of swarm systems -- Containment control of swarm systems -- Formation-containment control of swarm systems -- Conclusions and future work.
Keywords: Control engineering; System theory; Control theory; Artificial intelligence; Control and Systems Theory; Systems Theory, Control; Complex Systems; Artificial Intelligence